PS-105 Application of failure mode and effects analysis on drug management process in cardiology inpatient unit. (25th February 2017) - Jeddou, K Ben; Aissa, I; Mbarka, F Ben; Abbassi, A; Baccar, H; Chouchane, N; Ouahchi, Z
Abstract : Background: Our hospital mission is to insure patient safety and quality of care. Evaluation and improvement of drug management processes are essential to prevent and limit iatrogenic events. Purpose: The present study aimed to assess the risk of drug management processes in a cardiology inpatient unit according to a proactive analysis: failure mode and effects analysis method (FMEA). Material and methods: A multidisciplinary study group was assembled and a process diagram was drafted, illustrating all steps of the hospital medication system in the cardiology inpatient unit. Failure modes that could occur were identified and classified according to their risk priority score (RPS), determined on the basis of the likelihood of occurrence, severity of the potential effect and the detection probability rated on a scale from 1 to 10. The most critical failures were selected by applying the Pareto principle which states that, for many events, approximately 80% of the effects come from 20% of the causes. The failures causes were closely examined by establishing Ishikawa diagrams in order to propose corrective and preventive actions. Results: The evaluation process detected 66 potential failures. The frequency of failure modes were as follow: 44% in the prescription step, 24% in the distribution step, 20% in the drug delivery step and 12% in supplies from the pharmacy step. RPS ranged from 11 to 466. The Pareto principle was used to select 35 failure modes that had the highest RPS (from 132 to 466). Among those potential failures, we selected 18 higher RPS which it was essential to act. 50% applied to the medical prescription step, 39% to the drug delivery step and 11% to the distribution step. Preventive measures, such as prescription computerisation or nominative individual drug delivery, have been proposed to address the most critical failures. These actions are to be applied in the short, medium and long term. Conclusion: FMEA was useful to aid in understanding process care, detecting possible failures and prioritising remedial interventions. Systematic use of proactive risk analysis is needed for continuous safety improvement of drug management processes in hospitals. References and/or acknowledgements: Special thanks to the multidisciplinary group members. No conflict of interest